2020
DOI: 10.1177/1098612x20960400
|View full text |Cite
|
Sign up to set email alerts
|

Decreased antithrombin activity and inflammation in cats

Abstract: Objectives The objective of this study was to determine if inflammatory markers are associated with antithrombin activity in cats. Methods For a retrospective population of 231 cats admitted to a referral hospital, antithrombin activity was classified as decreased (n = 77), intermediate (n = 97) or in the upper quartile (n = 57). Odds ratios (ORs) were calculated for an association between decreased or upper quartile activity and hypoalbuminemia, hyperfibrinogenemia, band neutrophilia and toxic change. Multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The 52 reports deemed neutral to the PECO question included 396 cats in total with suspected IMHA in all of its forms (primary and secondary IMHA, pure red blood cell aplasia [PRCA] and nonregenerative immune‐mediated hemolytic anemia [NRIMHA]). There was no report of thrombosis in any of these studies 32–83 . In addition, these 52 reports included multiple other studies describing arterial and venous thrombosis in cats.…”
Section: Peco Question: Immune‐mediated Hemolytic Anemia (Imha) (Cats)mentioning
confidence: 99%
See 4 more Smart Citations
“…The 52 reports deemed neutral to the PECO question included 396 cats in total with suspected IMHA in all of its forms (primary and secondary IMHA, pure red blood cell aplasia [PRCA] and nonregenerative immune‐mediated hemolytic anemia [NRIMHA]). There was no report of thrombosis in any of these studies 32–83 . In addition, these 52 reports included multiple other studies describing arterial and venous thrombosis in cats.…”
Section: Peco Question: Immune‐mediated Hemolytic Anemia (Imha) (Cats)mentioning
confidence: 99%
“…Several of the reports describing histopathologic changes in cats with PLN or glomerulonephritis had evidence of fibrin deposition; however, none of the studies that reported histopathology described any micro‐ or macrovascular thrombosis 84,85 . Numerous studies were considered neutral to the PECO question because they did not include a control group, they described arterial thrombosis and did not mention PLN, or they were reports focused on PLN that did not discuss or describe thrombosis 45,48,49,54,59,62,63,66–68,70,86–110 . Although these reports were considered neutral, their collective weight suggests that there is either no association or a very weak association between PLN and arterial thromboembolic complications in cats and that the overall risk of thrombosis in cats with PLN is seemingly low.…”
Section: Peco Question: Protein‐losing Nephropathy (Pln) (Cats)mentioning
confidence: 99%
See 3 more Smart Citations